CLINICO-RADIOLOGICAL FINDINGS IN PEDAL MYCETOMA—A CASE REPORT - MUNIVENKATAPPA, KRISHNA KUMAR; Lokesh. C; Senthilnathan. V (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
One of the common granulomatous disorders affecting the skin and subcutaneous soft tissues, Madura mycosis or mycetoma is typically observed in tropical areas. Early diagnosis of mycetoma, which may be treated, depends on radiological imaging. Recently, the